Millennium Fleas Production Sdn. Bhd. / Siti Eliana Azyze Ezami Azyze ... [et al.] - Ezami Azyze, Siti Eliana Azyze; Mohamed, Marlia; Salieh Jolhie, Jozzieyana; Khalid, Maria; Zainai, Zairul Azwan (Faculty of Communication and Media Studies, 2002)
Millennium Fleas Production Sdn Bhd is a company that caters in designing, be it the print or electronic media. In this globalisation era, ICT play a major role in the business sector. The emergence of K-Economy had calls for professional workers to contribute in the growth of the country. We see that there is need for the K-Economy business to spread their wings and we have the solution